Dysregulated diurnal cortisol patterns are associated with cardiovascular mortality: Findings from the KORA-F3 study. (July 2022) - Karl, Sebastian; Johar, Hamimatunnisa; Ladwig, Karl-Heinz; Peters, Annette; Lederbogen, Florian
Abstract: Psychosocial stress has been associated with an increased risk for cardiovascular disease and death. Dysregulated diurnal cortisol slopes, which have also been associated with stress, might mediate this association. However, existing evidence on the cardiovascular health consequences of dysregulated cortisol slopes remains limited and inconclusive. To elucidate whether dysregulated diurnal cortisol slopes are related to cardiovascular mortality, we assessed salivary cortisol and cardiovascular morbidity and mortality in 1090 participants from the KORA-F3 study, a prospective, observational cohort study of a random representative sample from the general population. Eighty-seven deaths were registered during the mean follow-up period of approximately 11 years, 31 of which were classified as cardiovascular deaths. A more pronounced cortisol awakening response was associated with a lower risk of cardiovascular mortality in the adjusted Cox proportional hazards analysis (HR 0.59 [95-%-CI 0.36–0.96], p = 0.03). A greater diurnal cortisol peak-to-bedtime ratio at baseline also predicted a decreased risk of cardiovascular mortality (HR 0.50 [95-%-CI 0.34–0.73], p 0.01) and a decreased risk of stroke (HR 0.71 [95-%-CI 0.55–0.92], p 0.01). Increased levels of late night salivary cortisol predicted a higher risk of cardiovascular mortality (HR 1.49 [95-%-CI 1.13–1.97], p 0.01) and an increased risk of stroke (HR 1.24 [95-%-CI 1.01–1.52], p = 0.04). There was no association between measures of cortisol and non-cardiovascular related mortality. In conclusion, dysregulated diurnal cortisol patterns are associated with cardiovascular mortality, while greater diurnal cortisol variation seems to have a protective effect. This adds evidence to suggest a pathophysiological role of diurnal cortisol secretion patterns in cardiovascular health. Highlights: Diurnal cortisol secretion patterns may play a pathophysiological role in cardiovascular health. A higher cortisol awakening response is associated with a lower risk of cardiovascular mortality. A steeper diurnal cortisol slope is associated with a decreased risk of cardiovascular mortality. A steeper diurnal cortisol slope is associated with a decreased risk of stroke. Increased late night salivary cortisol is associated with a higher risk of cardiovascular mortality.